Power system oscillations damping using unified power flow controller-based stabilizer - Hassan, L.H.; Moghavvemi, M.; Mohamed, H.A.F. (Science Publications, 2010)
Problem statement: The Phillips-Heffron model of a power system with UPFC published by AJAS, demonstrates the effect of the UPFC in improving power system oscillation stability. Unfortunately, some of the equations have not been correctly derived and so working with this model in its existing form is misleading. Approach: In this study, the model is revisited and the equations are re-derived obtaining correct results. Three-machine power system installed with a UPFC is used to investigate the validity of these equations. Results: The simulation results demonstrated that the corrected model with an effective controller is active on damping of the low-frequency oscillations under different operating conditions. Conclusion: The corrected model works properly with power system networks for enhancing power system stability.